Assessment of environmental factors associated with dengue spread in an urban area of Puducherry - R., Abinaya; A., Velavan; Purty, Anil J.; N., Murugan (International Journal Of Community Medicine And Public Health, 2018)
Background: Dengue virus infection is an important global public health issue. Dengue disease burden in India is one of the highest in the world. Dengue is transmitted by Aedes mosquitoes which breeds mostly in water stagnated in artificial containers in and around the home surroundings. Puducherry reported an increased incidence of dengue cases in the recent years. Hence this study was done to assess the environmental risk factors associated with dengue transmission. Methods: A community based cross sectional study was done in 200 households of Solai Nagar, an urban area in Puducherry. Assessment of home environment and examination of the house holds for the presence of breeding sites of dengue mosquitoes and its larvae was done and socio demographic details, details of protective measures against dengue practiced by the respondents were obtained. Results: More than 80% of people live in pukka houses. There was no open defecation practice in this area and 90% of households disposed their solid waste through municipality. On assessing the breeding sites of Aedes mosquitoes, potted plants with saucer were found in high number (355) in 30% of the houses, air coolers in 17% of the houses. Discarded junks and discarded food container, disposal cups and coconut shells were present in many of the houses. Less than 40% of households only used at least one type of protective measures against dengue. Conclusions: The study area had abundant potential breeding sites of Aedes mosquitoes and the protective measures followed by the residents against mosquito bites were not adequate.